Astroblastomas exhibit radial glia stem cell lineages and differential expression of imprinted and X-inactivation escape genes - Norman L. Lehman; Nathalie Spassky; Müge Sak; Amy Webb; Cory T. Zumbar; Aisulu Usubalieva; Khaled J. Alkhateeb; Joseph P. McElroy; Kirsteen H. Maclean; Paolo Fadda; Tom Liu; Vineela Gangalapudi; et al. (Nature Communications, 2022)
Astroblastoma (AB) is an uncommon brain tumour and its origin remains unknown. Here, the authors perform integrative molecular analysis of 35 AB-like tumours and provide evidence that these arise in the context of epigenetic and genetic changes in neural progenitors occurring during brain development.